The Rising Cost of Cyberattacks: Trends and Impacts across Industries - Saif Al-Deen H. Hassan; Ali Abulridha Rasheed; Alaa Abdulshaheed Mousa; Zahraa Abed Hussein; Bhavna Ambudkar (HighTech and Innovation Journal)
Cybersecurity incidents have escalated sharply since 2020, exposing organizations to mounting financial and operational risks. This study quantifies multi-year trends in five major attack classes, calculates the compound annual growth rate (CAGR) of breaches, and evaluates how targeted security spending mitigates losses across eight industries. Secondary data were extracted from authoritative sources (IBM, ENISA, and Ponemon). Descriptive statistics charted incident growth; Pearson correlation assessed the linkage between phishing volume and breach frequency; ordinary least-squares regression measured the effect of network, infrastructure, and identity-access investments on breach counts. Breaches rose at a 28.3% CAGR from 2020 to 2023. Healthcare incurred the highest mean cost per incident (USD 10.9 million in 2023). Phishing volume strongly correlates with breaches (r = 0.97, p < 0.05), while greater outlays on network and infrastructure security were significantly associated with lower breach rates (β = –0.18 and –0.22, respectively; p < 0.05). Unlike prior sector-specific studies, our cross-industry analysis blends global data with inferential modelling, producing actionable benchmarks that help decision-makers allocate limited cybersecurity budgets where they reduce risk most.